Pitfalls in the diagnostic evaluation of subacute combined degeneration. (14th May 2015) - Ulrich, A; Müller, D; Linnebank, M; Tarnutzer, A A
Abstract : We report a case of a 43-year-old man presenting with a 2-week history of painless ascending sensory disturbances, suspected to be suffering from acute inflammatory polyneuropathy. On clinical examination, deep tendon reflexes were preserved and muscle strength was 5/5 everywhere. Gait was ataxic with positive Romberg test. Lumbar puncture was normal and electroneurography demonstrated demyelination. With spinal cord involvement centred on the posterior tracts on MRI, differential diagnosis focused on cobalamin deficiency. Initial laboratory work up showed nearly normal holotranscobalamin (43 pmol/L, normal>50) suggesting no vitamin B12 deficiency. Surprisingly, further testing including methylmalonic acid (3732 nmol/L, normal<271) and homocysteine (48.5 µmol/L, normal<10) showed an impairment of vitamin B12 -dependent metabolism leading to the diagnosis of subacute combined degeneration. Only after repeated history taking did the patient remember having taken tablets containing cobalamin for 3 days before hospitalisation. In case of B12 deficiency, holotranscobalamin can rapidly normalise during supplementation, whereas methylmalonic acid and homocysteine might help to detect B12 deficiency in patients who recently started supplementation.